Education responses to COVID-19: Implementing a way forward - Gouëdard, Pierre (OECD Education Working Papers, 2020)
During the COVID-19 crisis, countries have implemented a range of measures to curb the educational impact of the pandemic. In times of emergency, speed in the implementation of responses is key, but evidence of what may work is limited, and constraints on resources and capacity are binding. A framework providing a coherent implementation perspective can save time and result in better outcomes. As countries explore ways forward to reopen schools and design new models of education that expand the borders of the physical schools through technology, this paper proposes a framework that can help governments structure the implementation strategy of their evolving education responses to COVID-19. It consists of a set of general recommendations and guiding questions that can inform the development of mid-term education strategies and, more broadly, help build school systems' resilience for potential education emergencies